Effect of different media components and process conditions on the productivity of phenolic compounds from palm oil mill effluent by local isolated strain - Idris, Zulkarnain Mohamed; Jamal, Parveen; Alam, Md. Zahangir (2009)
The present investigation is an effort to develop an environmentally sound and cost effective fermentation process by introducing a new potential strain of Aspergillus niger which was isolated locally for the production of phenolics from palm oil mill effluent (POME). The selection of the potential fungal strain was done previously by screening seven strains and strain A103, which gave the highest total phenolic content after 72 hours of fermentation at fixed media and process conditions was used in this study. To enhance the production of phenolic compounds, a study based on statistical design was employed. A two-level Plackett-Burman design was applied where 11 variables consisted of various media components and process conditions were studied for their influence on phenolics production. Out of 11 variables, sucrose, manganese sulfate (MnSO4), and temperature were identified as the most significant variables in improving phenolics production by A103 strain. Single factor optimization for the selected variables was performed to further the optimization for the phenolics production. After the optimization, total phenolic content increased significantly from 856.09 to 940.80 GAE mg/l. The optimum conditions were found at a temperature of 35.0°C, 6.0% (w/v) sucrose, and 2.5% (w/v) MnSO4, with other fixed parameters. Surprisingly, the scavenging activity of the fermented extract on 2,2-diphenyl-1- picrylhydrazyl (DPPH) radical showed almost 95% of inhibition. The activity was higher compared to butylated hydroxytoluene (BHT), a synthetic antioxidant which showed only 91% of inhibition, with promising applications in food and pharmaceutical industries.